Process and Determinants of Cross-Border Migration of Nepalese People of India - Kunwar, Laxman Singh (Tribhuvan University Journal, 2018)
Cross border migration between Nepal and India has long history with unique dimensions. This paper highlights the migration process and determining factors of cross border migrants of Nepalese people to India. Some literatures related with migration between Nepal and India as well as main migration theories including their debates are highlighted. The study households were selected randomly by using systematic random sampling method. The information was collected through field study by using structured and semi structured questions. The participation of ancestors in cross border, sources of information, accompanies of migrants and decision makers for cross border migration were analyzed in migration process. Main reasons of crossing the border, employment situation, poverty and income, land holding size, indebtedness and frequencies of migrants crossing the border by themselves were concluded the main determining factors in cross border migration.